The method of hierarchy analysis in modeling the strategy of formation of innovative potential - I. S. Klimenko (Современная наука и инновации, 2024)
The article develops a mathematical model of innovation potential management. The analysis of the factors influencing the innovation climate is carried out, an attempt is made to justify the expediency of applying mathematical modeling methods to the processes of managing the innovation climate. The author considers the main stages of strategic planning; the main content of the study is devoted to the integration of modeling methods into the practice of innovation management. Because of the research, the author comes to the conclusion about the need for the integrated use of formal and informal modeling methods in the system of formation and development of the innovative potential of economic entities.